MODELING OF ORE-MAGMATIC SYSTEM OF GOLD DEPOSITS IN EASTERN KAZAKHSTAN - Мізерна, М.; Оразбекова, Г.; Д'ячков, Б.; Мирошникова, А.; Зацерковний, В. (Київський національний університет імені Тараса Шевченка, 2020)
The article is devoted to the results of using system-defined geological modeling for forecasting gold deposits on the territory of the oldest gold mining region in the Republic of Kazakhstan – the West Kalba gold belt (East Kazakhstan). Research is aimed at developing forecast criteria and searches for new ore objects in favorable geological structures. The main attention of the conducted research was focused on a system-defined analysis of geological factors, the interaction of which provides a synergy effect and reveals the patterns of formation of gold ore objects. To solve this problem, the authors made a quantitative assessment of the development sustainability of the ore-generating elements of the system according to S.V. Vasiliev methodology. A quantitative assessment of the stability of individual factors and their interaction made it possible to assess the qualitative state of individual sections and define the natural boundaries of the areas of the corresponding hierarchical level, promising for the search of certain mineral deposits. The specific work was carried out to define the areas promising for the search of deposits based on a quantitative assessment of the individual factors stability. Using geological materials, results of geophysical work, space-geological data, the localization of promising areas within the West Kalba structural-formation zone and the Zhumba ore-magmatic system in East Kazakhstan was done.

Присвячено результатам використання системного геологічного моделювання при прогнозуванні золоторудних родовищ на території найстарішого району видобутку золота в Республіці Казахстан – Західно-Калбінського золоторудного поясу (Східний Казахстан).Дослідження спрямовані на розробку критеріїв прогнозу і пошуку нових рудних об'єктів у сприятливих геологічних структурах. Головнаувага при проведенні досліджень була приділена системному аналізу геологічних факторів, взаємодія яких забезпечує синергетичнийефект і виявлення закономірностей формування золоторудних об'єктів. Для розв'язку цієї задачі авторами здійснена кількісна оцінкастійкості розвитку рудогенеруючих елементів системи за методикою С.В. Васильєва.Кількісна оцінка стійкості окремих факторів та їхньої взаємодії дозволили оцінити якісний стан окремих ділянок і визначити природні границі площ відповідного ієрархічного рівня, перспективних на пошуки родовищ певної корисної копалини.Були виконані роботи з виділення площ, перспективних на пошуки родовищ, на основі кількісної оцінки стійкості окремих факторів.З використанням геологічних матеріалів, результатів геофізичних робіт, космогеологічних даних проведено локалізацію перспективних площ у межах Західно-Калбінської структурно-формаційної зони і Жумбинської рудно-магматичної системи у Східному Казахстані.
МОДЕЛЮВАННЯ МАГМАТОГЕННИХ РУДНИХ СИСТЕМ ЗОЛОТОРУДНИХ РОДОВИЩ СХІДНОГО КАЗАХСТАНУ
Keywords: рудно-магматична система; золото; родовище; оцінка стійкості геологічних факторів; ore-magmatic system; gold; deposit; assessment of the geological factors stability